On-treatment serum albumin levels can predict 28-day mortality and guide albumin infusion in sepsis patients - Ren, Danfeng; Dang, Xiangyun; Ni, Tianzhi; Zhou, Jingwen; Zhang, Ze; Fu, Shan; Zhang, Wentao; Yan, Taotao; Zhao, Yingren; Liu, Jinfeng (Frontiers in Medicine, 2025)
BackgroundAs the most abundant protein in plasma, albumin (ALB) presents close association with prognosis of septic patients. Whereas, the benefit and the target level of ALB infusion remain controversial.MethodsWe conducted a retrospective investigation to assess whether on-treatment ALB levels could predict 28-day mortality and try to identify the optimal level for ALB infusion. All patients diagnosed as sepsis from January 2016 to December 2020 were recruited and re-evaluated using Sepsis-3 criteria.ResultsA total of 199 eligible patients were enrolled in this study. Compared with the survival group, the non-survival group had more males (73.97 vs. 56.35%), older patients (62.78 ± 15.93 vs. 56.43 ± 18.46), and a higher proportion of Gram-positive bacterial infection (27.40 vs. 23.02%), higher Sequential Organ Failure Assessment (SOFA) score (7.00–13.00 vs. 6.00–12.00), higher APACHE II score (18.25–29.00 vs. 15.00–26.00), higher PCT (2.84–49.18 vs. 2.43–19.14), more patients with septic shock (65.75%vs. 43.65%), shorter ICU-stay days (11.04 ± 6.28 vs. 14.83 ± 8.58), longer mechanical ventilation days (7.23 ± 7.07 vs. 5.04 ± 8.52), with statistically significant differences (p < 0.050). Furthermore, we identified that the ALB level on day 7 (HR, 0.920; 95% CI, 0.847 to 0.999; p = 0.046) and the maximum ALB level within the first 14 days (HR, 0.900; 95% CI, 0.838 to 0.967; p = 0.004) were independent protective factor for the 28-day prognosis in septic patients. Moreover, ROC curve analysis indicated that optimal target level for first 14-day maximum and on day 7 were 33.45 g/L and 27.85 g/L, respectively. Correspondingly, a negative correlation between ALB level and mortality was defined with Kaplan–Meier survival curve analysis. Further subgroup analysis showed that the group with ALB above the cut-off value was associated with favorable outcomes in female patients under 60 years, with SOFA score less than 7, and APACHE II score less than 19.ConclusionALB levels on day 7 and the maximum ALB level within first 14 days after ICU admission were closely associated with 28-day mortality. 27.85 g/L would work as the target level of ALB infusion on 7 day to improve the prognosis of sepsis patients.